Transforming private landlords : housing, markets and public policy - Crook, Tony, 1944- (Real estate issues (Oxford, England), 2010)
This book explores the origins, extent and implications of this revival in the fortunes of private landlordism. It presents an in-depth, scholarly analysis of private landlords, the rationales for and ways in which governments have sought to revitalise investment in residential lettings, and their success in doing so. It also assesses the extent to which landlordism has been transformed in recent years and the lessons for policy that can be learned from this experience. The book draws on the extensive research into private landlords conducted by the authors over the past two decades. This incl.